2023
DOI: 10.1007/s40894-022-00202-8
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Mental Health Literacy Measures for Children and Adolescents

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Process interventions were put in place to increase feasibility of the RCT in Czechia. For example, we conducted a systematic review to identify tools available for the assessment of MHL in children and adolescents (Kucera et al, 2023) where we found no existing measures designed for universal populations of young adolescents, therefore we developed a tool to measure this process outcome of interest (Kågström et al, 2023). Additionally, we collaborated with CSI to ensure that any schools being inspected for framework adherence had exemption to deliver On My Mind as an exception in cases where schools were randomized into the intervention arm of the RCT but did not have time to adapt their framework in time to deliver the curriculum within health education.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Process interventions were put in place to increase feasibility of the RCT in Czechia. For example, we conducted a systematic review to identify tools available for the assessment of MHL in children and adolescents (Kucera et al, 2023) where we found no existing measures designed for universal populations of young adolescents, therefore we developed a tool to measure this process outcome of interest (Kågström et al, 2023). Additionally, we collaborated with CSI to ensure that any schools being inspected for framework adherence had exemption to deliver On My Mind as an exception in cases where schools were randomized into the intervention arm of the RCT but did not have time to adapt their framework in time to deliver the curriculum within health education.…”
Section: Methodsmentioning
confidence: 99%
“…As mental health evidence grows, it will be increasingly important to use quality tools to assess interventions, especially well-conducted cluster RCTs to provide strong evidence for future implementation and to scale it up (Wei et al, 2013) to increase feasibility of the RCT in Czechia. For example, we conducted a systematic review to identify tools available for the assessment of MHL in children and adolescents (Kucera et al, 2023) where we found no existing measures designed for universal populations of young adolescents, therefore we developed a tool to measure this process outcome of interest (Kågström et al, 2023).…”
Section: Stage 3: Evaluationmentioning
confidence: 99%
“…Therefore, improv-ing MHL has been highlighted as a crucial factor in preventing and treating mental disorders. 10,11 Furthermore, seeking informal help, including through family or friends, can result in delayed treatment and recovery. 9 This means that the level of understanding and trust in professional resources influences the selection of resources and health behaviors.…”
Section: Mental Health Literacymentioning
confidence: 99%
“…Low MHL results in low awareness of the need for treatment, which is consistently identified as the biggest obstacle to treatment and recovery. Therefore, improving MHL has been highlighted as a crucial factor in preventing and treating mental disorders [ 10 , 11 ]. Furthermore, seeking informal help, including through family or friends, can result in delayed treatment and recovery [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation